Entre ruas e singularidades: uso e apropriação do espaço público na Vila Belga em Santa Maria - RS - Magoga, Milena Rubin (2023)
This research aims to understand the dynamics of use and appropriation of public space of the street in Vila Belga, located in Santa Maria, Rio Grande do Sul. In this perspective, a focus is proposed on the particularities and subjectivities that directly influence the constitution of the analyzed territory, as well as the different overlapping temporalities in the space. The theoretical foundation involves themes such as: the use and appropriation of the street for different activities; the atmospheres and experiences that emerge from the place; and the use of images as a tool in the investigative process. The adopted methodology includes cartography, used as a research positioning during field studies, and interviews, conducted to expand the collective understanding of the space. The results, revealed through the application of methodological procedures, allowed contact with new peculiarities of the place. In the interviews, images were an important instrument to access residents' sensations, affective memories, and connections with the space, highlighting the formation of a united community and the intrinsic link with the past. In this scenario, the interpretations and guidelines generated from the intersections of data and visual aspects can contribute both to mitigate identified problems and to expanding positive characteristics involving the use of the street in Vila Belga. The conclusions point to the relevance of examining the appropriations of public space, based on the uniqueness of the place, as well as the investigative potential of images in the research process.